Energy Management System Comparison Among Fuzzy Strategies - Julio C. Pena-Aguirre; Francisco J. Perez-Pinal; Yosafat J. Samano-Flores; Alejandro I. Barranco-Gutierrez; Gilberto Gonzalez Gomez; Tomas Serrano-Ramirez (IEEE Access)
This study evaluates and compares energy management systems (EMS) for hybrid vehicles using fuzzy logic strategies to optimize energy distribution between fuel cells (FC) and batteries. Key components, including the Proton Exchange Membrane Fuel Cell (PEMFC) and the Permanent Magnet Synchronous Motor (PMSM), were modeled and validated using MATLAB-Simulink, LabVIEW, and Hardware-in-the-Loop (HIL) testing. The proposed EMS achieves the highest efficiency, up to a fuel cell average power output of 8.5 kW, an efficiency of 74.35%, and a state of charge (SoC) improvement of 34.25%. Other strategies, including those of (Esoufi et al., 2020, Hemi et al., 2014, and Zhao et al. 2021), exhibited average power outputs ranging from 7.28 to 7.79 kW and SoC improvements of 22.96% to 28.35%. These results emphasize the advantages of the proposed strategy fuzzy logic-based EMS in balancing energy demands, reducing battery stress, and extending battery life under urban driving conditions. The findings highlight fuzzy logic as a superior approach to traditional methods for managing hybrid vehicle powertrains, particularly in scenarios with frequent acceleration and deceleration.